The challenge of complexity and the possible role of public ethics - Taccogna, Gerolamo (P.A. Persona e Amministrazione, 2023)
The paper deals with complexity as perceived by jurists, as the result of social pluralism, highlighting on the one hand the overcoming of conceptions aimed at governing it through reductionist authoritarianism and, on the other hand, the problems deriving from the lack of ideologies and values sufficiently shared and perceived in society. The awareness of the interconnection, interaction and feedback between individuals and social formations, together with the strong evolution of technical knowledge and digitization, push towards new horizons, also with regard to key concepts such as democracy and that of legitimizing public power. The legal paradigms, which have already evolved over time, must be adapted. Representation (even with all its problematic aspects) retains its own role, but appears destined to increasingly hybridize with other forms of participation. In this framework, public ethics, especially if developed in the form of legal discipline of politics and political action (still largely absent), can provide an important contribution by favoring a recovery of credibility of institutions and public apparatuses and, therefore, a support for desirable spontaneous rearrangements of society, in the sense of cooperation between its parts and hopefully the reconquest of some unifying elements. The perspective remains, however, not that of tension towards a static ideal objective, but that of an accompaniment of irrepressible dynamics and evolutions of the substratum of law.